Attenuation of Late-Stage Disease in Mice Infected by the Mycobacterium tuberculosis Mutant Lacking the SigF Alternate Sigma Factor and Identification of SigF-Dependent Genes by Microarray Analysis - Geiman, Deborah E. (American Society for Microbiology, 2004)
The Mycobacterium tuberculosis alternate sigma factor, SigF, is expressed during stationary growth phase and under stress conditions in vitro. To better understand the function of SigF we studied the phenotype of the M. tuberculosis ΔsigF mutant in vivo during mouse infection, tested the mutant as a vaccine in rabbits, and evaluated the mutant's microarray expression profile in comparison with the wild type. In mice the growth rates of the ΔsigF mutant and wild-type strains were nearly identical during the first 8 weeks after infection. At 8 weeks, the ΔsigF mutant persisted in the lung, while the wild type continued growing through 20 weeks. Histopathological analysis showed that both wild-type and mutant strains had similar degrees of interstitial and granulomatous inflammation during the first 12 weeks of infection. However, from 12 to 20 weeks the mutant strain showed smaller and fewer lesions and less inflammation in the lungs and spleen. Intradermal vaccination of rabbits with the M. tuberculosis ΔsigF strain, followed by aerosol challenge, resulted in fewer tubercles than did intradermal M. bovis BCG vaccination. Complete genomic microarray analysis revealed that 187 genes were relatively underexpressed in the absence of SigF in early stationary phase, 277 in late stationary phase, and only 38 genes in exponential growth phase. Numerous regulatory genes and those involved in cell envelope synthesis were down-regulated in the absence of SigF; moreover, the ΔsigF mutant strain lacked neutral red staining, suggesting a reduction in the expression of envelope-associated sulfolipids. Examination of 5′-untranslated sequences among the downregulated genes revealed multiple instances of a putative SigF consensus recognition sequence: GGTTTCX(18)GGGTAT. These results indicate that in the mouse the M. tuberculosis ΔsigF mutant strain persists in the lung but at lower bacterial burdens than wild type and is attenuated by histopathologic assessment. Microarray analysis has identified SigF-dependent genes and a putative SigF consensus recognition site.